أساليب القصر في سورة الملك وترجمتها إلى اللغة الإندونيسية في كتاب تفسير العشر الأخير: Asalib al-Qashr fi Surah al-Mulk wa Tarjamatuha ila al-Lugah al-Indunisiyyah fi Kitab Tafsir al-’Asyr al-Akhir
ولا تزال دراسة أساليب لغة القرآن مستمرة حتى الآن، لأن بنية اللغة القرآنية وأسلوبها لهما مزايا مختلفة. والهدف من هذا البحث هو معرفة إعجاز القرآن من نوع الأسلوب اللغوي الوارد في سورة الملك، وهو أسلوب القصر المتضمن في دراسة علم المعانى، وكذلك معرفة ترجمة أساليب القصر في سورة الملك إلى اللغة الإندونيسية. وكان هذا البحث من البحث النوعي مع استخدام طريقة تحليل المضمون. ولتحليل البيانات قام الباحثون بتحليل أنماط الجمل (الآيات) التي تدخل في فئة أساليب القصر وطريقة الترجمة لها. والنتائج المحصولة فهي( 1) ثمانية أنماط لأسلوب القصر في سورة الملك بطرق مختلفة مثل الاستثناء, وإنما, والتقديم ما حقه التأخير ( 2 ) الترجمة لكل واحدة من هذه الطريقة. ولذلك فإن نتائج هذا البحث مفيدة في إثراء اللغة وتنمية المعرفة، لا سيما فيما يتعلق بدراسة علم المعاني وهو مرجع أساسي في فهم معنى القرآن بشكل صحيح. Abstract The study of the Qur’an’s Uslub (style) is ongoing, because the structure and style of the Qur’an have numerous benefits. The purpose of this research is to discover one of the Qur’anic miracles from the type of language style contained in Surat al-Mulk, namely the Qasr language style included in the study of Asalib al-Ma’ani, as well as the translation of the meaning of the Qasr language style in Surat al-Mulk into Indonesian. This study applied qualitative research with content analysis methods. To analyse data, researchers examine sentence patterns (verses) that fall into the Qasr category, as well as translation methods. The findings of this study are as follows: 1) There are eight Qasr patterns in Surat al-Mulk, each with its own method, such as Ististna, Innama, and precedence that should come last; and 2) translation of each Qasr method. As a result, the findings of this study have implications for a wealth of knowledge, particularly those related to the study of Ma’a>ny science, and serve as the foundation for correctly understanding the content of the Qur’an. , number=1, journal=Diwan: Jurnal Bahasa dan Sastra Arab, author=Syafei, Isop and Yonan, Yonan, year=2023, month=Jun., pages=1–18